DSA techniques for fast and robust acquisition of DS - Kim, Byoung-Hoon (IEEE Communications magazine)
This article introduces the key concepts, organization, and operations of distributed sample-based acquisition (DSA) systems, which have previously been introduced for fast and robust synchronization of the long-period scrambling codes in DS/CDMA environments. In DSA systems, the transmitter samples and sends the state of its main sequence generator, or main shift register generator (SRG), in a distributed manner over the short-period igniter sequence, and the receiver detects and applies the state samples to correct the state of its main SRG, thereby acquiring SRG synchronization after a round of state reception. Acquisition performance of DSA techniques is extremely fast and robust compared to typical correlation-based acquisition techniques of comparable complexity. This article discusses the operation and performance of DSA techniques in the DS/CDMA communication environment as well as their applications to intercell synchronous and asynchronous cellular systems.